Tax compliance costs and small business performance: Evidence from the South African construction industry - Obert Matarirano; Germinah E. Chiloane-Tsoka; Daniel Makina (South African Journal of Business Management, 2019)
Background: Several studies on tax compliance costs (TCCs) for small businesses found them to be regressive in nature and, imposing a heavier burden on small businesses compared to larger ones.Objectives: This study predicts the effect of TCCs on performance of small businesses using the survival index value model (SIV®). The intention is to determine if TCCs have a statistically significant effect on the performance of small businesses.Method: A self-administered questionnaire was emailed to randomly selected contractors registered in classes 3 and 4 of the Construction Industry Development Board to solicit responses. Paired samples t-tests, Pearson correlation coefficient tests, regression tests and structural equation modelling were carried out on the 83 responses obtained.Results: Data analysis, using STATA data analysis and statistical software, depicted TCCs to have a significant effect on the performance of small businesses. Internal TCCs were found to have the heaviest burden on small businesses, and thus had the strongest impact on performance. External TCCs were found to have a negative effect on business performance.Conclusion: The article recommends proper tax planning for small businesses to enjoy the benefits associated with TCCs and minimise the negative effects. To improve on their performance, small businesses are advised to undertake tax tasks in-house.
Keywords: 650